Simulasi Turbin Portabel Jenis Cross Flow Untuk Pembangkit Listrik Tenaga Pikohidro (PLTPH) - Triyono, Budi; Yudrika, Moh Azmil; Setiawan, Dibyo (JURNAL CRANKSHAFT, 2024)
In Indonesia, especially West Java Province, there are quite a lot of rivers with quite high or mountainous elevation differences, generally, these rivers are used as tourist attractions which are located far from residential areas. To meet electricity needs, an alternative is to convert the river flow into electricity, either used for lighting or simply to charge electronic devices such as gadgets. One solution is to make small turbines that can be moved and can be produced in large quantities. Through this activity, a simulation analysis will be carried out on previously available designs so that existing weaknesses can be seen so that they can become evaluation material for subsequent designs. The stages of activities carried out include the study stage of simulations using CFD to determine deficiencies in inflow performance and also serve as material for the evaluation of subsequent designs. From the results of the simulation that has been carried out, the flow in the existing equipment has a decrease when it hits the cross-flow turbine blade so that the flow is not at its optimal speed, besides that the kinetic energy has not been completely converted into mechanical energy which can be seen in the velocity distribution picture, namely the flow still has a speed when it enters the outlet hole, this becomes a loss for the tool and becomes a note for evaluation for further tool design.